Variation of morphology, karyotype and protein band pattern of adenium (Adenium obesum) varieties - DWI HASTUTI; SURANTO SURANTO; PRABANG SETYONO (Smujo International, 2009)
Hastuti D, Suranto, Setyono P. 2009. Variation of morphology, karyotype and protein band pattern of adenium (Adenium obesum) varieties. Nusantara Bioscience 1: 78-83. The aim of this research to find out the Adenium obesum variation from six varieties, namely: obesum, cery, red lucas, red fanta , white bigben and harry potter based on morphology, karyotype, as well as protein banding pattern. The chromosome preparation was made using semi-permanent squash method from the tip of root plant; while protein banding pattern was made using SDS-PAGE method. Qualitative data included shape and color of the leave and flower described from each variety. Data were presented in morphometry and analyzed using ANOVA and then followed by DMRT with 5% of confidence levels, indicated significance difference. Protein banding pattern, the root, stem, leave and all organs were analyzed using Hierarchical Cluster Analysis method with Average Linkage (between Groups) using SPSS 10.0. The result of research shows that the six A. obesum varieties have morphological character with no variation of light green to dark green leave, not hairy, smooth leave bone, meanwhile for light red to dark red flower crown color although some of them are white and the same funnel color, yellow. All varieties of A. obesum have same number of chromosome, 2n = 22 and shows the difference ranging from 2.56 to 5.13 μm. In the banding pattern formed qualitatively, there is variation among the six varieties.